DIAGNOSING THE COVERAGE GAP OF THE CHRONIC DISEASE MANAGEMENT PROGRAM AT X PRIMARY HEALTH CENTER - Henri Perwira Negara; Rinawati (Journal of Social and Economics Research, 2025)
Non communicable diseases such as diabetes mellitus and hypertension constitute a major health burden in Indonesia and place growing pressure on the national health insurance system. BPJS Kesehatan launched the Chronic Disease Management Program Prolanis to strengthen monitoring, medication adherence, and patient education through primary care services, yet national reports indicate that only a small fraction of eligible patients are registered and even fewer achieve clinical control. This study diagnoses the gap between the target and actual coverage of Prolanis at X Primary Health Center. A qualitative descriptive case study was conducted from January to September 2025 with purposively selected participants, including one program coordinator, six healthcare workers, four community health volunteers, and four program participants. Data were collected through in depth interviews, observations of program activities, and analysis of monthly reports and participant registers, then thematically analyzed at organizational, team, and individual levels. With 298 diabetes and 1,250 hypertension patients, the target of five percent controlled participants was exceeded for diabetes only in February and March and was never met for hypertension. Enabling factors included leadership commitment, supportive policies, team cohesiveness, and staff motivation, while barriers involved the absence of integrated standard operating procedures, limited information tools, inefficient workflows, staff and training shortages, and low health literacy. Prolanis coverage at X Primary Health Center remains far below the target, indicating that organizational redesign and stronger community engagement are required to improve coverage and clinical control.